2017
DOI: 10.1093/alcalc/agx107
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Alcohol Hangovers: Not Just a Matter of Being Resilient

Abstract: The current findings suggest that having a hangover is not simply an expression of poor psychological coping with the next-day consequences of heavy alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
1
14
3
Order By: Relevance
“…A recent study looked into biopsychological characteristics of hangover sensitive and hangover resistant drinkers, including mental resilience and perceived immune status [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study looked into biopsychological characteristics of hangover sensitive and hangover resistant drinkers, including mental resilience and perceived immune status [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also outside the context of alcohol hangover, van Schrojenstein Lantman et al demonstrated the existence of interrelationships between mental resilience, self-reported immune functioning, and health [ 15 ]. In a first analysis [ 9 ] we compared mental resilience of hangover resistant drinkers and hangover sensitive drinkers. It was hypothesized that alcohol is an example of a stressor, and that hangover resistance of certain drinkers may be explained by having higher levels of mental resilience than hangover sensitive drinkers.…”
Section: Introductionmentioning
confidence: 99%
“…Differences found between the two eBAC methods used in this study suggest that additional research exploring the accuracy and comprehensiveness of eBAC equations is needed for future (naturalistic) hangover research. As illustrated earlier, previous alcohol hangover research most commonly uses the modified Widmark calculations for BAC [ 3 , 31 , 32 , 33 ]. Previous research suggests that higher levels of BAC (0.11%) were needed to develop a next day hangover.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the modified formula optimised the calculation of total amount of body water and included height and age [ 28 ]. The updated equations are found to be reasonably accurate for eBACs under controlled laboratory environments [ 28 , 29 , 30 ] and are frequently used in present alcohol hangover research to estimate BACs [ 3 , 31 , 32 , 33 ]. Please refer to Appendix B for additional information.…”
Section: Introductionmentioning
confidence: 99%
“…Data show that this claim heavily depends on how much alcohol drinkers consume, but even at higher eBAC levels a small proportion of drinkers claim not to have hangovers [27,28]. At the same time, other hangover research showed no significant differences between the two groups of drinkers on several biomarkers such as urine ethyl glucuronide (EtG) and ethyl sulfate (EtS) [57] or methanol [58], saliva cytokine levels [59], sensitivity to acute alcohol effects [60], demographics [31], or psychological characteristics such as mental resilience [61]. Additionally, the current study could not differentiate hangover-sensitive and hangover-resistant drinkers based on their dietary nutrient intake.…”
Section: Discussionmentioning
confidence: 99%